Policy Uncertainty and Customer Concentration - Leung, Woon Sau; Sun, Jiong (Production and Operations Management, 2021)
Using data involving customer–supplier relationships and a large sample of US publicly listed firms, our study documents a negative and statistically significant relationship between economic policy uncertainty and firms’ customer‐base concentration. The negative relation is predominant in firms with higher inventory efficiency and those operating in competitive, high‐R&D, and nondurable industries. Customer‐base diversification is further shown to enhance firm performance during periods of increasing policy uncertainty, but not when policy uncertainty decreases. Overall, our evidence suggests that firms respond to increasing policy uncertainty by diversifying their customer base and such behavior contributes positively to firm performance.